Graft-versus-lymphoma effect after reduced intensity allogeneic hematopoietic stem cell transplantation from HLA-two loci mismatched father in a patient with refractory non-Hodgkin lymphoma - Suminoe, Aiko; Matsuzaki, Akinobu; Koga, Yuhki; Hatano, Miho; Hara, Takuya; Hara, Toshiro (The Turkish Journal of Pediatrics, 2009)
A 10-year-old female developed a mediastinal mass and was diagnosed as mixed lineage lymphoblastic lymphoma. The tumor was extremely refractory, and she never achieved remission despite intensive therapy using 12 anti-lymphoma agents and local irradiation. She received reduced-intensity allogeneic peripheral blood stem cell transplantation from her HLA-two loci mismatched father, and achieved complete remission. However, the lymphoma relapsed four months later, and we abruptly discontinued immunosuppressive drugs. Concurrent with the development of grade III graft-versus-host disease, the lymphoma completely disappeared with an increase of activated T-cells in peripheral blood. The clinical course suggested the graft-versus-lymphoma effect against aggressive/refractory lymphoma.